Automated analysis of cerebrospinal fluid cells using commercially available blood cell analysis devices: a critical appraisal - Wick, Manfred; Gross, Catharina C.; Tumani, Hayrettin; Wildemann, Brigitte; Stangel, Martin (Cells, 2021)
The analysis of cells in the cerebrospinal fluid (CSF) is a routine procedure that is usually performed manually using the Fuchs-Rosenthal chamber and cell microscopy for cell counting and differentiation. In order to reduce the requirement for manual assessment, automated analyses by devices mainly used for blood cell analysis have been also used for CSF samples. Here, we summarize the current state of investigations using these automated devices and critically review their limitations. Despite technical improvements, the lower limit for reliable leukocyte counts in the CSF is still at approximately 20 cells/µL, to be validated depending on the device. Since the critical range for clinical decisions is in the range of 5-30 cells/µL this implies that cell numbers < 30/µL require a manual confirmation. Moreover, the lower limit of reliable erythrocyte detection by automated devices is at approximately 1000/µL. However, even low erythrocyte numbers may be of clinical importance. In contrast, heavily hemorrhagic samples from neurosurgery may be counted automatically at an acceptable precision more quickly. Finally, cell differentiation by automated devices provides only a rough orientation for lymphocytes, granulocytes and monocytes. Other diagnostically important cell types such as tumor cells, siderophages, blasts and others are not reliably detected. Thus, although the automation may give a gross estimate sufficient for the emergency room situation, each CSF requires a manual microscopy for cytological evaluation for the final report. In conclusion, although automated analysis of CSF cells may provide a first orientation of the cell profile in an individual sample, an additional manual cell count and a microscopic cytology are still required and represent the gold standard.